2021
DOI: 10.1098/rspa.2021.0457
|View full text |Cite
|
Sign up to set email alerts
|

Modelling song popularity as a contagious process

Abstract: Popular songs are often said to be ‘contagious’, ‘infectious’ or ‘viral’. We find that download count time series for many popular songs resemble infectious disease epidemic curves. This paper suggests infectious disease transmission models could help clarify mechanisms that contribute to the ‘spread’ of song preferences and how these mechanisms underlie song popularity. We analysed data from MixRadio, comprising song downloads through Nokia cell phones in Great Britain from 2007 to 2014. We compared the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Studies of classical music have found that melodic intervals are associated with particular historical periods (Rodriguez Zivic et al, 2013;Weiß et al, 2019;Harasim et al, 2021), and that tonal complexity and harmonic richness have increased over time ( Weiß et al, 2019;Serra-Peralta et al 2021). Studies of contemporary and popular music have tracked changes in a variety of music characteristics such as diversity, loudness, and the emotional valence of lyrics (Mauch et al, 2015;Serrà et al, 2012;Napier and Shamir, 2018;Brand et al, 2019), and have used detailed information on population structure and the distribution of cultural variants to try to understand the processes underlying such changes (Youngblood, 2019b;Klimek et al, 2019;Youngblood et al, 2021;Rosati et al, 2021). Experimental approaches have shown that rhythms and melodies increase in regularity over the course of transmission in a manner that is consistent with universal cognitive priors that are mediated by both individual experience and external factors (Ravignani et al, 2017;Jacoby et al, 2021;Lumaca and Baggio, 2017;Ravignani et al, 2018;Miton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of classical music have found that melodic intervals are associated with particular historical periods (Rodriguez Zivic et al, 2013;Weiß et al, 2019;Harasim et al, 2021), and that tonal complexity and harmonic richness have increased over time ( Weiß et al, 2019;Serra-Peralta et al 2021). Studies of contemporary and popular music have tracked changes in a variety of music characteristics such as diversity, loudness, and the emotional valence of lyrics (Mauch et al, 2015;Serrà et al, 2012;Napier and Shamir, 2018;Brand et al, 2019), and have used detailed information on population structure and the distribution of cultural variants to try to understand the processes underlying such changes (Youngblood, 2019b;Klimek et al, 2019;Youngblood et al, 2021;Rosati et al, 2021). Experimental approaches have shown that rhythms and melodies increase in regularity over the course of transmission in a manner that is consistent with universal cognitive priors that are mediated by both individual experience and external factors (Ravignani et al, 2017;Jacoby et al, 2021;Lumaca and Baggio, 2017;Ravignani et al, 2018;Miton et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, songs from di erent genres appear to spread more rapidly through populations, likely depending on cultural context. For example, contagion models t to song download data from Nokia cell phones in the UK between 2007 and 2014 show that electronic music spread much more rapidly than other genres during that time period (Rosati et al, 2021). We suspect that such variation in genre popularity over time and space is at least partly driven by fashion cycles (Acerbi et al, 2012).…”
Section: Contemporary and Popular Musicmentioning
confidence: 99%
“…Yet, unbeknownst to the political level at the time, music offers a valuable means to connect people safely and seamlessly with exceptional speed across long distances despite societal shutdowns-and this capacity increases manifold when mediated by modern information technology. In fact, recent epidemiological modelling of download count time series data established that the electronica music genre has a basic reproduction number (R0) of 3,430, making it about 190 times as 'contagious' as measles (Rosati et al 2021). This revitalizes strong imagery of 'viral tunes' promoted in public discourse and serious science (e.g., Fink et al 2021).…”
Section: Setting the Scenementioning
confidence: 99%
“…As a result, the SIR model remains a useful tool at such global level of description. Besides, epidemiologic thinking can be used, either with the SIR model or variants thereof, to model the spread of rumours Daley & Kendall (1964), songs Rosati et al (2021) or singer popularity Tweedle & Smith (2012) as well as fashion Acerbi et al (2012) and fads on the internet Bauckhage et al (2013), making the SIR model an active subject of research, nearly a century after having been put forward 2 of 15 GREGORY KOZYREFF by Kermack & McKendrick (1927). We write it as follows dS dt = −β SI/N,…”
Section: Introductionmentioning
confidence: 99%